A synthesis of barriers to and enablers of pro-poor climate change adaptation in four South African municipalities. (4th July 2018) - Spires, Meggan; Shackleton, Sheona E.
Abstract : Qualitative case studies were undertaken to explore the multiple, interacting factors that hinder and/or facilitate planned pro-poor climate change adaptation in four South African municipalities. A comparison of barriers and enablers across the cases revealed several key themes. Municipalities struggle to implement climate change adaptation within contexts of significant social, economic and ecological challenges. These contextual barriers, when combined with certain cognitive barriers, led to reactive responses. Existing municipal systems and structures make it difficult to enable climate change adaptation, which is inherently cross-sectoral and messy. Lack of locally applicable knowledge, funding and human resources were found to be significant resource barriers, and were often underlain by social barriers relating to perceptions, beliefs and governance challenges. Enablers of engaged officials, operating within conducive organizational environments and drawing on partnerships and networks, were able to circumvent these barriers to some extent. When enablers coincided with windows of opportunity that increased prioritization of climate change, projects with ancillary benefits were implemented. The implications of these results are discussed and suggestions made for how pro-poor municipal planned climate change adaptation that responds to the needs of vulnerable communities can be further understood and enabled in the future.